Right and Yet Wrong: A Spatio-Temporal Evaluation of Germany's Covid-19 Containment Policy - Michael Berlemann; Erik Haustein (Center for Economic Studies and Ifo Institute (CESifo), 2020)
In order to get the Covid-19 pandemic under control, most governments around the globe have adopted some sort of containment policies. In the light of the enormous costs of these policies, in many countries highly controversial discussions on the adequacy of the chosen policies evolved. We contribute to this discussion by evaluating three waves of containment measures adopted by the German government. Based on a spatio-temporal endemic-epidemic model we show that in retrospective, only the first wave of containment measures clearly contributed to flattening the curve of new infections. However, a real-time analysis using the same empirical model reveals that based on the then available information, the adoption of additional containment measures was warranted. Moreover our spatio-temporal analysis shows that a one-size-fits-all policy, as it was adopted in Germany on the early stages of the epidemic, is not optimal.
Keywords: I12; I18; 330; containment measures; policy uncertainty; Covid-19; SIR model; infections; spatio-temporal modeling